Natural Compounds With Antibacterial Activity Against Cronobacter spp. in Powdered Infant Formula: A Review - Polat Yemiş, Gökçe; Delaquis, Pascal (Frontiers in Nutrition, 2020)
Bacteria from the genus Cronobacter are opportunistic foodborne pathogens capable of causing severe infections in neonates, the elderly and immunocompromised adults. The majority of neonatal infections have been linked epidemiologically to dehydrated powdered infant formulas (PIFs), the majority of which are manufactured using processes that do not ensure commercial sterility. Unfortunately, the osmotolerance, desiccation resistance, mild thermotolerance and wide-ranging minimum, optimum and maximum growth temperatures of Cronobacter spp. are conducive to survival and/or growth during the processing, reconstitution and storage of reconstituted PIFs. Consequently, considerable research has been directed at the development of alternative strategies for the control of Cronobacter spp. in PIFs, including approaches that employ antimicrobial compounds derived from natural sources. The latter include a range of phytochemicals ranging from crude extracts or essential oils derived from various plants (eg. thyme, cinnamon, clove, marjoram, cumin, mint, fennel), to complex polyphenolic extracts (eg. muscadine seed, pomegranate peel, olive oil and cocoa powder extracts), purified simple phenolic compounds (eg. carvacrol, citral, thymol, eugenol, diacetyl, vanillin, cinnamic acid, trans-cinnamaldehyde, ferulic acid) and medium chain fatty acids (monocaprylin, caprylic acid). Antimicrobials derived from microbial sources (eg. nisin, other antibacterial peptides, organic acids, coenzyme Q0) and animal sources (eg. chitosan, lactoferrin, antibacterial peptides from milk) have also been shown to exhibit antibacterial activity against the species. The selection of antimicrobials for the control of Cronobacter spp. requires an understanding of activity at different temperatures, knowledge about their mode of action, and careful consideration for toxicological and nutritional effects on neonates. Consequently, the purpose of the present review is to provide a comprehensive summary of currently available data pertaining to the antibacterial effects of natural antimicrobial compounds against Cronobacter spp. with a view to provide information needed to inform the selection of compounds suitable for control of the pathogen during the manufacture or preparation of PIFs by end users.